Clinical trial characteristics and intervention profiles for mild cognitive impairment: a systematic analysis of WHO ICTRP registry - Sun, Yingxuan; Zhang, Fengwei; Zhou, Yinghong; Yuan, Yonggen; Li, Mengjia; Xu, Ji; Deng, Hongyong (Frontiers in Pharmacology, 2026)
IntroductionMild cognitive impairment (MCI) is a cognitive decline syndrome that represents an intermediate stage between normal aging and dementia, with a high risk of progression to dementia. The World Health Organization’s International Clinical Trials Registry Platform (WHO ICTRP) is the world’s largest clinical trial registry, aggregating data from global registries. This study aimed to analyze MCI trials in the ICTRP to delineate the research landscape, key focus areas, and emerging trends in MCI to inform future intervention strategies.MethodsA systematic study was performed to analyze MCI clinical trials registered in the ICTRP up to December 2024. Records were deduplicated, and extracted variables included study design, phase, country, sponsor, sample size, intervention type, and outcomes. Dual independent extraction was performed, with third-party adjudication for discrepancies.ResultsA total of 2,609 MCI trials were included, with 51.8% registered in the past five years. The United States led in the number of registrations among countries, whereas Asia topped the list among continents. Of all the trials, 2,064 were interventional trials, while 499 were observational trials. Predominant types of interventions were non-pharmacological therapies, including non-invasive brain stimulation (211), cognitive interventions (194), computer-assisted cognitive interventions (192), dietary interventions (187), and exercise interventions (184). In the realm of pharmacological therapies, chemical drugs were the most prevalent. Clinical trials were concentrated in Phase 0/II. Most trials were sponsored by universities. In addition, 60.1% of the trials included fewer than 100 participants, and data sharing occurred at a low level.Conclusion MCI trial registrations have been increasing annually. The treatment of MCI focuses on non-pharmacological therapies, with most pharmacological therapy studies in the early stages of clinical trials. Notably, integrated cognitive training that combines traditional methods with computer-assisted technologies has emerged as a particularly promising area of research.